The Influence of Training Programs on Employee Work Performance at the South Makassar I Regional Revenue Technical Implementation Unit (UPTP) Office - Hawadi, Muhammad Taufik; Kurniawan, Agung Widhi; Natsir, Uhud Darmawan; Sahabuddin, Romansyah; Dipoatmodjo, Tenri Sayu Puspitaningsih; Aswar, Nurul Fadilah (prodima@fe.uika-bogor.ac.id, 2023)
This study aims to determine the significance of the Influence of the Training Program on Employee Work Performance at the UPTP Office of the South Makassar I Region, the method in this study was collecting data through questionnaires and observation. The population in this study were 40 employees. With a sample of 40 employees, the results of this study indicate that training has a positive and significant effect on employee performance.